A Descriptive Study on Quality of Life among Adolescents with Beta-Thalassemia Major in the Maldives - Mansoor, Shanooha; Othman, Zahiruddin; Othman, Azizah; Husain, Maruzairi (Japan International Cultural Exchange Foundation, 2018)
Background: The Maldives has the highest prevalence of thalassemia in the world. However, there is little research done on the psychosocial aspects of this illness. Objectives: This study aimed to examine health related quality of life (HRQOL) among adolescents with beta-thalassemia major attending the National Thalassemia and Other Hemoglobinopathies Centre (NTC), Maldives Blood Services, Maldives. Thus, appropriate recommendation could be proposed. Methods: A total of 81 adolescents (mean age 15.7 years) with beta-thalassemia major were engaged. HRQOL was assessed using the Pediatric Quality of Life Inventory (PedsQL). Other relevant information was gathered through interview or medical record. Results: The HRQOL was reduced. The mean for physical, emotional, social, school and psychosocial HRQOL was 80.50, 72.30, 88.18, 76.44, and 78.96, respectively. The total HRQOL was 79.50 and this was lower in females (75.29) compared to males (83.29). Ferritin levels of 1,001-2,499 μg/l and > 2,500 μg/l were noted in 34.2% and 53.9%, respectively. Good compliance was reported in 55% of participants. Conclusions: Adolescents with beta-thalassemia major in the Maldives have reduced HRQOL. The high ferritin level could reduce the HRQOL and hence an attempt should be made towards lowering ferritin and improving compliance to chelation treatments. The gender difference in HRQOL signifies the need for more attention to the female patients and for areas of improvement to be explored